Hong Kong Public Social Communication Strategies in a Demonstration Against the Proposed Extradition Law - Rico Rico; Siti Fatimah; Muzahid Akbar Hayat (Journal of Social Science, 2021)
Hong Kong, one of the global financial centers, was plunged into chaos for almost two months straight from June to July 2019. For eight weeks, demonstrations by the Hong Kong people have been going on and on until they become violent. The demonstration was intended to deny the proposed extradition law, which would allow Hong Kong prisoners, including foreigners, to be extradited to China. The extradition bill is also called to threaten the freedom of local people, to threaten democracy and law in the Hong Kong region. The different political systems between China and Hong Kong make the relationship both vulnerable. As a special region in China, Hong Kong needs to get the attention of the Chinese government by conceding its rights and upholding its systems so that demonstrations need not be too worried. Hong Kong people are making a variety of attempts at demonstration and even some social communication strategies are used to reject the traditional bill. The method used in this study is qualitative deskriftive with case studies of direct observation of sites and several demonstration articles in Hong Kong. As a result of this study, several unique strategies of Hong Kong's demonstrations have been carried out to maintain a message being delivered by another group that the Hong Kong government has even brought attention to the world.